To feel rewarded as a parent: be compassionate with yourself - De la Vega Castelo, Ariadna Maria; Pedroso-Chaparro, María del Sequeros; Romero-Moreno, Rosa; Nogales-González, Celia; Vagos, Paula; Vara-García, Carlos (Anales de Psicología / Annals of Psychology, 2025)
Being a parent is associated with positive outcomes. However, other than having a child, the predictors for such outcomes are scarcely studied in the literature. The current study analyzes the association between self-compassion, parental stress, and parenting rewards (e.g., joy, happiness, and satisfaction taken from the role of parenting) in parents of children with and without disabilities aged 0-6. 169 parents (69.8% female; 26.03% taking care of a child with a disability) completed a self-report questionnaire assessing levels of self-compassion, parental stress, and parenting rewards. A path model examined the effect of self-compassion on parenting rewards, moderated through parental stress and controlling for age and gender. Results suggest that higher levels of self-compassion are associated with higher levels of parenting rewards through lower levels of parental stress. Invariance analyses suggest that this relationship depends on whether the child has a disability. Specifically, a direct association between self-compassion and parenting rewards was identified only among parents caring for children without disabilities. The results suggest that enhancing self-compassion in parents may reduce stress, and therefore, be linked to higher levels of joy, happiness, and satisfaction in performing the parental role. This supports self-compassion as key to parenting and has clinical implications.